A HOTS-Based Digital Pop-Up Book on the Human Digestive System Improves Elementary School Students' Critical Thinking Skills - Ni Nengah Mery Handayani; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (International Journal of Natural Science and Engineering, 2024)
The low critical reasoning ability of elementary school students shows the weakness of the learning process that encourages students to think at a higher level. This is exacerbated by the lack of use of innovative learning media and learning activities that do not demand active student involvement. This study aims to develop and test the feasibility of digital pop-up book learning media on the human digestive system based on HOTS. The type of research used is development research with the ADDIE model. The research subjects consisted of 2 material experts, 2 media experts, 2 design experts, 3 teachers, 3 students for individual trials, 9 students for small group trials, 15 control group students, and 23 experimental group students at the implementation stage. Data were collected through questionnaires and tests, using instruments in the form of rating scales and multiple-choice questions. The data analysis techniques used include qualitative and quantitative descriptive analysis. The results showed that the media was considered feasible to use based on the validation of experts and positive responses from teachers and students. The use of this media also proved effective in improving students' critical reasoning skills, which was shown through the difference in results between the control and experimental groups. The conclusion of this study states that HOTS-based digital pop-up book is a feasible, practical, and effective learning medium to be used in elementary schools. The implication is that interactive digital media can be an innovative alternative in developing higher-order thinking skills.